Cost Of Illnes As A Basic For Advocacy Efforts to Prevent An Increase In The Prevalence of Type 2 Diabetes Mellitus - Qomariyah, Nurul Laily; Rochmah, Thinni Nurul; DM, Rizka Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Diabetes mellitus is a chronic disease that requires continuous treatment. This can result in an economic burden on sufferers. One method that can be used in analyzing the economic burden due to a disease is the Cost of Illness method by calculating the direct and indirect costs of sufferers and program costs that have been incurred by the government. The purpose of this study was to analyze the Cost of Illness in type 2 diabetes mellitus patients. This research was a quantitative descriptive cross-sectional approach. The sampling technique used multistage random sampling and obtained a sample size of 144 type 2 diabetes mellitus patients from hospitals and health centers in Bulungan Regency, North Kalimantan. The results of the analysis of the Cost of Illness for type 2 diabetes mellitus patients in Bulungan Regency amounted to Rp.7,350,237 per patient each year. The results of the calculation of the Cost of Illness for type 2 diabetes mellitus patients can be used to advocate that promotive and preventive programs are the main focus of disease control, and promote a social security system to offset the direct costs of individuals, so that the entire population can be protected from the high Cost of Illness. Keywords: Cost of illness, Diabetes Mellitus, promotive, preventive